2011
DOI: 10.1007/s10532-011-9522-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Pseudomonas sp. DX7 capable of degrading sulfadoxine

Abstract: Given that the intensive application of sulfonamides in aquaculture, animal husbandry and malaria treatment has lead to an increase in sulfonamide discharge into the environment, there is an increasing need to find a way to remediate sulfonamide-contaminated sites. The bacterial strain DX7 was isolated from a marine environment and is capable of degrading sulfadoxine. DX7 was identified as a Pseudomonas sp.based on 16S rRNA gene sequencing. Approximately 30% of sulfadoxine was degraded after Pseudomonas sp. DX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…strain Jpyr-1 [26], and sulfadoxine by Pseudomonas sp. DX7 [27]. In this study, a pure bacterial strain identified to the genus Pseudomonas was isolated and efficiently degraded QPE.…”
Section: Resultsmentioning
confidence: 99%
“…strain Jpyr-1 [26], and sulfadoxine by Pseudomonas sp. DX7 [27]. In this study, a pure bacterial strain identified to the genus Pseudomonas was isolated and efficiently degraded QPE.…”
Section: Resultsmentioning
confidence: 99%
“…Among all these methods, biodegradation has been proved to be an advanced technique to remove various pollutants from the environment. In our lab, efforts were made to investigate the biotransformation of heavy metals, and biodegradation of sulfonamide drugs, nitrofurans drugs, and EDCs by bacterial strains and their potential application in bioremediation (Zhang et al 2012a(Zhang et al , 2012b(Zhang et al , 2012c(Zhang et al , 2013. Bacterial community is readily catabolized to BPA, and BPA-degrading bacterial strains were isolated and identified from various environments (Kang et al 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…The cell pellets were washed twice with sterilized phosphate buffer (PBS), and adjusted to OD 600 of approximately 1. Zhang et al (2012). Briefly, bacterial cells were cultured in 10 ml MTM containing 5 mg l À1 FZD at 28 C for 2 days, and cells were pelleted by centrifugation at 10,000 Â g for 5 min.…”
Section: Fzd Degradation By Bacterial Strainsmentioning
confidence: 99%